Perspektif Pelanggan BSC Pendidikan dalam Meningkatkan Pelayanan Prima pada STAI Kuala Kapuas - Iim Wasliman; Sofyan Tsauri; Akhmad Maki; Bidin Bidin; Khalifaturrahmah Khalifaturrahmah (Journal on Education, 2023)
The development of the Kuala Kapuas Islamic College of Religion must be followed by management that is modern and oriented towards high performance. Performance measurement by considering financial and non-financial perspectives is known as the balanced scorecard developed by Kaplan and Norton. The balanced scorecard is a modern performance measure by considering four perspectives which are the translation of strategies and goals to be achieved in the long term. In this study the method used is a descriptive analysis method using primary and secondary data analysis. The results showed that the needs analysis of the design of performance measurement using the Balanced Scorecard at STAI Kuala Kapuas, begins with translating the vision, mission and goals and analyzing the situation and strategic position as the ideals of STAI Kuala Kapuas in the long term into activities in the short term, which then used as material for designing a performance measurement framework with the Balanced Scorecard at STAI Kuala Kapuas